Business & Economics - BE-ci 2016 : Proceedings of the Proceedings of the 3rd International Conference on Business & Economics (BE-ci 2016) /: Proceedings of the Proceedings of the 3rd International Conference on Business & Economics (BE-ci 2016). (2016) - Unknown
No abstract available